Respuesta :

Answer:

w = 2

Step-by-step explanation:

Distribute the expression and compare like terms with the simplified version.

Given

wx(3y² + 6y - 2) ← distribute parenthesis

= 3wxy² + 6wxy - 2wx

Compare coefficients of like terms with

6xy² + 12xy - 4x

Compare xy² term, then

3w = 6 ( divide both sides by 3 )

w = 2

Compare xy term, then

6w = 12 ( divide both sides by 6 )

w = 2

Compare x term, then

- 2w = - 4 ( divide both sides by - 2 )

w = 2

Hence the required value of w is 2

Answer:

-7

Step-by-step explanation: